The Use of Operating Cash Flow and Managerial Ownership Against Accounting Conservatism - Nursita, Meta; Ratnasari, Fina; Handayani, Puspita (Majalah Ilmiah Bijak, 2025)
This study investigates the impact of operating cash flow and managerial ownership on accounting conservatism in the financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research employs a purposive sampling method, with a sample size of 57 companies listed on the IDX within the specified period. The data analysis process includes descriptive statistical testing, multicollinearity testing, overall model testing, regression model feasibility testing, and hypothesis testing. Panel data regression analysis is the statistical method utilized in this research. The findings reveal that operating cash flow partially influences accounting conservatism, managerial ownership also has a partial effect on accounting conservatism, and collectively, both variables significantly impact accounting conservatism. The study aims to provide practical value, enabling businesses and the public to better understand the role of operating cash flow and managerial ownership in fostering accounting conservatism, particularly in companies listed on the IDX.